Historic hybridization and introgression between two iconic Australian anemonefish and contemporary patterns of population connectivity - van der Meer, M.; Jones, G.; Hobbs, Jean-Paul; Van Herwerden, L. (John Wiley & Sons, 2012)
Endemic species on islands are considered at risk of extinction for several reasons, including limited dispersal abilities, small population sizes, and low genetic diversity. We used mitochondrial DNA (D-Loop) and 17 microsatellite loci to explore the evolutionary relationship between an endemic anemonefish, Amphiprion mccullochi (restricted to isolated locations in subtropical eastern Australia) and its more widespread sister species, A. akindynos. A mitochondrial DNA (mtDNA) phylogram showed reciprocal monophyly was lacking for the two species, with two supported groups, each containing representatives of both species, but no shared haplotypes and up to 12 species, but not location-specific management units (MUs). Population genetic analyses suggested evolutionary connectivity among samples of each species (mtDNA), while ecological connectivity was only evident among populations of the endemic, A. mccullochi. This suggests higher dispersal between endemic anemonefish populations at both evolutionary and ecological timeframes, despite separation by hundreds of kilometers. The complex mtDNA structure results from historical hybridization and introgression in the evolutionary past of these species, validated by msat analyses (NEWHYBRIDS, STRUCTURE, and DAPC). Both species had high genetic diversities (mtDNA h > 0.90, p= 4.0%; msat genetic diversity, gd > 0.670). While high gd and connectivity reduce extinction risk, identifying and protecting populations implicated in generating reticulate structure among these species should be a conservation priority.